The problem of training social teachers in the Republic of Kazakhstan - Yersultanova, G.S.; Baymakhanova, U.M.; Amanova, A.K.; Kuanysheva, B.T. (Акад. Е.А. Бөкетов ат. Қарағанды ун-ті КЕАҚ баспасы, 2023)
This article is devoted to a topic relevant to the 21st century, the topic of training social educators. The historical facts connected with the use of the term “social pedagogy” in science and practice, with the peculiarities of the development of this science in different countries of the world are noted. At the same time, the issue of the development of this science in the Republic of Kazakhstan is considered in detail. The urgency of the problem of training social educators is related to the fact that previously part of the functions performed by a social educator was performed by the school’s deputy director for educational work. Namely, work with children with deviant behavior, prevention and timely detection of negative phenomena, work with children from large families, etc. Currently, a new round is being planned in the profession of a social pedagogue. This can be seen from the analysis of the activities of universities of the Republic of Kazakhstan for the training of social educators. The authors of the article analyzed the curricula of higher educational institutions in Kazakhstan implementing educational programs for the training of social educators. New approaches to the training of social educators imply the expansion of their functions by including the functionality of a tutor in general or a tutor of inclusive education in particular.
Қазақстан Республикасында әлеуметтік педагогтерді дайындау мәселесі
Проблема подготовки социальных педагогов в Республике Казахстан
Keywords: social pedagogy; socialization of personality; social worker; deviant behavior; inclusive education; pedagogy; social work; educational program